2013
DOI: 10.1161/circulationaha.113.001533
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Promotes Sex-Independent Angiogenesis in Response to Ischemia and Is Required for Activation of Vascular Endothelial Growth Factor Receptor Signaling

Abstract: Background Hypoandrogenemia is associated with an increased risk of ischemic diseases. Since actions of androgens are exerted through androgen receptor (AR) activation, we studied hind limb ischemia in AR knockout (KO) mice to elucidate the role of AR in response to ischemia. Methods and Results Both male and female ARKO mice exhibited impaired blood flow recovery, more cellular apoptosis and a higher incidence of autoamputation after ischemia. In ex vivo and in vivo angiogenesis studies, AR-deficient vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 59 publications
0
47
1
Order By: Relevance
“…In addition, DHT, through activation of the AR, promoted in vitro angiogenic processes such as EC migration, proliferation, and tubulogenesis via VEGF-related mechanisms in ECs derived from male donors 74,75) . In contrast, we demonstrated that both male and female AR knockout mice showed impaired revascularization after ischemia despite a robust increase of VEGF expression 36) . Moreover, endothelial cells from AR knockout mice had attenuated angiogenic potency.…”
Section: Androgens Are Associated With Arterial Diseases In Humansmentioning
confidence: 58%
See 4 more Smart Citations
“…In addition, DHT, through activation of the AR, promoted in vitro angiogenic processes such as EC migration, proliferation, and tubulogenesis via VEGF-related mechanisms in ECs derived from male donors 74,75) . In contrast, we demonstrated that both male and female AR knockout mice showed impaired revascularization after ischemia despite a robust increase of VEGF expression 36) . Moreover, endothelial cells from AR knockout mice had attenuated angiogenic potency.…”
Section: Androgens Are Associated With Arterial Diseases In Humansmentioning
confidence: 58%
“…Sieveking et al reported that DHT induced dose-dependent increases in the mRNA expression of KDR, a major VEGF receptor, in male HUVECs 75) . We also demonstrated that AR activation is required for the compensatory up-regulation of KDR gene expression in response to ischemia, at least in male mice 36) . Previous studies revealed that a ternary complex formed among AR, PI3Kp85, and Src is essential for the androgen-stimulated activation of PI3K/Akt and mitogen-activated protein kinase 88,89) and that KDR is activated by the recruitment and activation of Src and PI3K 90) .…”
Section: Ar Does Not Have Any Influence On Bone Marrow-derived Endothmentioning
confidence: 60%
See 3 more Smart Citations